Workplace Violence, University Staff Job Performance, and Mediation - Godbless, Eromafuru Edward; Enoh, Ikpesu (The journal of contemporary issues in business and government, 2022)
Quite expansive works have been undertaken to gauge incessant spate of violence at workplace particularly as it relates to general job performance; not much have been done in the case of non- academic staff of Nigerian Universities. Furthermore, while work-related violence has been thought to associate with burnout and negative job behavior, there have been growing concerns among organizations to be preoccupied with economic gains rather than the long-term human impacts of their decisions. The purpose of the study is to explore how workplace violence (WKPLV) through occupational stress (OCPST) affects staff performance (STAFP) of non- academic employees of federal universities in Nigeria. The population of the study totaled 13873, comprises 8045 (senior) and 5828 (junior) non-academic staff of federal universities. Research approach involved Quasi-Experimental Design and sample size of 389 randomly determined; Multiple Regression and Structural Equation Modeling deployed as analytical tools; Reliability was affirmed at: WKPLV (0.975); STAFP (0.987); and OCPST (0.985). The regression result, juxtaposed by sample response showed evident of significant but negative relationship between WKPLV and STAFP. There are strong statistical underpinnings that occupational stress mediates the effects of WKPLV on performance.. We propose that management of universities in act proactively by bracing up plans to investigate factors that precipitate violence at work and checkmating them so as to minimize their stress-induced effects on performance. Research implications, study originality and research limitations are discussed.